Relationship between maternal cardiovascular diseases risk factors during pregnancy and low birth weight in neonates by Case-Control Method - Mehdi Rajaei; Yousef Vaisani; Reza Najafi; Ali Delpisheh (Mashhad University of Medical Sciences, 2019)
Introduction: Low birth weight (LBW) is a very sensitive and useful index for child's health. Therefore, evaluation of the related risk factors is very noticeable. So, this study was performed with aim to determine the relationship between maternal cardiovascular diseases risk factors and low birth weight risk in neonates. Methods: This case-control study was conducted in 2018 on 250 newborn infants, of which 125 with low birth weight were considered as case group and 125 with normal weight as control group. They were randomly selected from eligible individuals. Data were analyzed by statistical tests including crosstab, t-test, Chi-square and logistic regression with regard to error less than α = 0.05. Results: Some risk factors of maternal cardiovascular diseases including physical inactivity (P = 0.007), exposure to smoke and tobacco (P = 0.005), triglyceride (P = 0.008), cholesterol (P = 0.028), salt intake (P = 0.004), inadequate consumption of fruit (P = 0.05), inadequate consumption of vegetables (P = 0.03), and consumption of fast food and drinks (P = 0.01) had significant relationship with LBW in neonates. Conclusion: According to the results of this study, some maternal risk factors of cardiovascular diseases such as exposure to tobacco smoke and smoking, salt intake, fast food and drinks, lack of fruits and vegetables consumption, lack of activity and high levels of triglyceride can be considered as risk factors for LBW.